On Combinatorial Optimization and Mechanism Design Problems Arising at Container Ports - Meiswinkel, Sebastian (Produktion und Logistik, 2018)
Sebastian Meiswinkel studies optimization problems that arise at container ports from a classic optimization as well as from a mechanism design point of view. The first part of this dissertation is focused on scheduling problems with selfish job owners that have private information about their characteristics. Afterwards the transportations of containers between the quay and a storage area is considered. Variants of this problem are analyzed for utilization of reach stackers and straddle carriers. Contents Truthful Algorithms for Job Agents The Partitioning Min-Max Weighted Matching Problem Straddle Carrier Routing at Container Ports with Quay Crane Buffers Target Groups Researchers and students in the fields of operations research, logistics, mathematics and game theory Practitioners in the areas of logistics and operations research The Author Dr. Sebastian Meiswinkel wrote his dissertation under the supervision of Prof. Dr. Erwin Pesch at the Department of Management Information Science at the University of Siegen.